ANALISIS KARAKTERISTIK SOSIAL EKONOMI YANG MEMANFAATKAN JASA PEGADAIAN DI KOTA MEDAN - Julita, Mawardi Nur (Jurnal Riset Akuntansi dan Bisnis, 2008)
In the preamble 1945 states that the aim of a state is to achieve the righteousand prosperous people. In order to support the great and independent nationaleconomy, the economic depelopment needs to get in appropriate order to increasethe people’s income and to overcome inbalanced economy and social gap. Thegovernment gives some service, protection and welfare as its responsibility, so eachpeople can fulfill their needs to gain the welfare for those people who live inIndonesia.This research made to know the characteristic of social economic peoplethat use the government services such as pawnshop in Medan. It made also to knowwhether there is a relationship or not between social economic characteristic andservice (the amount of money owed) in the pawnshop and to find out the mostdominant social economic characteristic in using the pawnshop in Medan.The number of sample in this research is 170 which consist of 17 pawnshopbranch offices in Medan. Each office was given a questionnaire for 10 person whoused the pawnshop’s service. The tenth person were taken randomly. In findings, thecharacteristics of social economy that is represented by the income’s factors, thenumber of families and educations affects the amount of money owed and the mostdominat factor of it is the consumer’s income and the numbers of families . Thecause is the consumer’s income that regarded as one of the terms which should beasked in having a loan, while the number of families is regarded as another cause ofthe amount of the money owed. The bigger of the number of families influenced thebigger needs, so that the pawnshop is chosen as the one of alternative ways to fulfilthe needs. The most dominant effect given by the social economic characteristic tothe amount of money owed is 55,7% and the rest is 44,3 % it is influenced by anotherfactors, such as the guarantee, the limit of time, the interest rate and administrationgiven to the consumers.